2014
DOI: 10.1063/1.4870532
|View full text |Cite
|
Sign up to set email alerts
|

Tuning magnetism of monolayer MoS2 by doping vacancy and applying strain

Abstract: In view of important role of inducing and manipulating the magnetism in two-dimensional materials for the development of low-dimensional spintronic devices, the influences of strain on electronic structure and magnetic properties of commonly observed vacancies doped monolayer MoS2 are investigated using first-principles calculations. It is shown that unstrained VS, VS2, and VMoS3 doped monolayer MoS2 systems are nonmagnetic, while the ground state of unstrained VMoS6 doped system is magnetic and the magnetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(155 citation statements)
references
References 41 publications
6
144
2
Order By: Relevance
“…This research is exemplified by calculations of the magnetic moment for different chemical compositions 20 and of straininduced magnetism. [23][24][25] Some of the published information is contradictory such as the reports of strain-dependent ferromagnetism 26 and antiferromagnetism 27 in NbX 2 (X ¼ S, Se) monolayers.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This research is exemplified by calculations of the magnetic moment for different chemical compositions 20 and of straininduced magnetism. [23][24][25] Some of the published information is contradictory such as the reports of strain-dependent ferromagnetism 26 and antiferromagnetism 27 in NbX 2 (X ¼ S, Se) monolayers.…”
mentioning
confidence: 91%
“…14 The properties of 2D TMDs vary from semiconducting (MoS 2 , WS 2 ) to metallic (NbSe 2 , TaS 2 ) and magnetic (VS 2 , VSe 2 ). [15][16][17][18] Very recently, it has become clear that 2D TMDs exhibit striking physical-property changes due to strain, 14,[19][20][21][22][23][24][25][26][27] chemical functionalization, [28][29][30][31][32][33] doping with transition metals, 34 and external electric fields. 35 For instance, it has been demonstrated experimentally that strain modulates the bandgap of monolayers and bilayers in MoS 2 .…”
mentioning
confidence: 99%
“…23 Zheng et al predicted by first-principles calculations that macroscopic ferromagnetism of MoS 2 nanosheets could be introduced by applying doping vacancy defects. 24 Cai et al found that the transformation of the surrounding 2H-MoS 2 local lattice into a trigonal MoS 2 could be prompted if introducing S vacancy in a 2H-MoS 2 ultrathin nanosheet host. Then, a robust intrinsic ferromagnetic response may be created.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the large magnetic moments and HRTEM image (Fig. S8, supplementary material) of the H(i) sample suggest that the non-magnetic V S2 -like defects 30 are much similar to the electron beaminduced 1 T phase 20 because the 1 T-phase incorporated MoS 2 samples via the chemical method induced the magnetism. 17,25 This may be a more simple way than a two-step hydrothermal method to intentionally introduce V S defects, which transform the local lattice surrounding the V S into 1 T phase.…”
Section: Fig 3 Hrtem Images Of (A) the Pristine Mos 2 And (B)-(e) Ementioning
confidence: 99%
“…21,23 Meanwhile, the theoretical study has reported that while the V S , V S2 , and V MoS3 vacancies doped monolayer MoS 2 systems are nonmagnetic, the tensile strain induces magnetic moments in these systems by breaking of Mo-Mo metallic bonds around the vacancies. 30 In fact, the distances between the two neighboring Mo atoms around such vacancies increase in the electron irradiated samples compared to the distance (a ¼ 3.12 Å ) 26 of the pristine MoS 2 (Figs. S6-S10, supplementary material).…”
Section: Fig 3 Hrtem Images Of (A) the Pristine Mos 2 And (B)-(e) Ementioning
confidence: 99%